2015
DOI: 10.5152/npa.2015.7226
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Early Postoperative Neurological Complications Following Living Donor Liver Transplantation

Abstract: Mortality was significantly higher and the duration of postoperative hospitalization significantly longer in LDLT patients with new-onset neurological complications than in those without such complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
(19 reference statements)
1
5
0
Order By: Relevance
“…We found a male to female ratio of 1.8:1 in our study group, which included 90 men (64.7%) and 49 women (35.3%). Otan et al (2015) found a male-to-female ratio of 1.8:1 among liver transplant recipients in Turkey, which is in line with other studies [18]. Among liver transplant patients, males outnumber females (1.6:1), Dhar et al…”
Section: Resultssupporting
confidence: 83%
“…We found a male to female ratio of 1.8:1 in our study group, which included 90 men (64.7%) and 49 women (35.3%). Otan et al (2015) found a male-to-female ratio of 1.8:1 among liver transplant recipients in Turkey, which is in line with other studies [18]. Among liver transplant patients, males outnumber females (1.6:1), Dhar et al…”
Section: Resultssupporting
confidence: 83%
“…The brain is one of them, and HIRI-related neurological complication includes encephalopathy, epileptic seizures, posterior leukoencephalopathy syndrome, infection, and central pontine myelinolysis [23]. These complications are closely associated with significant mortality and morbidity and lead to a longer duration of postoperative hospitalization [24]. In addition, the incidence of neurological complication after pediatric liver transplantation, which resulted from biliary atresia and other protopathy, is as high as 46% due to the vulnerability of a developmental brain [25].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the blood concentration of tacrolimus had little effect on NCs (p > 0.1). Although many reports have previously stated that tacrolimus is an independent risk factor for NCs (Otan et al, 2015a), most transplant centers currently have more positive experience in the administration of tacrolimus, which may help reduce the incidence of NCs. We also compared the dosasge of tacrolimus and found no statistical difference between the two groups (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that up to 30% of the patients in western countries developed neurological complications after LT, but only 4% after heart transplantation and 0.5% after renal transplantation (Agildere et al, 2006, Amodio et al, 2007, Bronster et al, 2000. Frequent complications include acute confusion, epilepsy, cerebrovascular disease (Otan et al, 2015a(Otan et al, , 2015b, and central system infection (Weiss and Thabut, 2019). These symptoms lead to a decline in the quality of life of patients, and even increase the mortality rate (Ghaus et al, 2001).…”
Section: Introductionmentioning
confidence: 99%